Flux of tritium from the sea to the atmosphere around a nuclear reprocessing plant: Experimental measurements and modelling for the Western English channel. (February 2023) - Connan, O.; Bailly du Bois, P.; Solier, L.; Hebert, D.; Voiseux, C.
Abstract: Tritium is released to the environment by nuclear industries in various forms, mainly HTO. In impact studies leading to estimated doses for the population, atmospheric discharges are mainly taken into consideration because they generally lead to values higher than those related to liquid discharges. However, the tritium released in liquid environments can be transferred to the atmosphere by evaporation and then be transported to terrestrial ecosystems by wind. This study was carried out in France near a fuel reprocessing plant (RP) which discharges tritium into the western English Channel. We highlighted the influence of a mass of water enriched with tritium on the HTO levels in atmospheric water vapour downwind through 18 field campaigns. A hydrodynamic model able to simulate tritium activity in the water was coupled with an evaporation an atmospheric transport model. It allows to reconstitute variations in atmospheric tritium on the coast, depending on liquid discharges of tritium from the reprocessing plant. On this basis, when seawater containing 20–100 Bq.L −1 of tritium flows between 0 and 10 km off the coast, variations in atmospheric activity onshore can increase of 2–15 Bq.L −1 . Mean tritium quantities released by the sea into the atmosphere in the Western English Channel reached 130 TBq.y −1 over the 2017–2020 period. Emissions were estimated at 0.9–11.3 GBq km −2 .y −1 and depends principally on the distance from the liquid discharge point. If we compare the "marine" source term, in HTO form, with the direct source term for gaseous discharges, the marine source term is one order of magnitude greater for the marine region affected by liquid discharges. Finally, we estimate that approximately 1.1% of tritium stock discharged at sea (regulated and controlled) return to the atmosphere each year at the scale of the Western English Channel. Highlights: Hydrodynamic modelling of tritium transport in seawater. Tritium exchange at interface sea– air by evaporation flux. Experimental measurements of HTO activities in the atmosphere. Calculating the amount of tritium emitted to the atmosphere by the Western English Channel. 1.1% of the tritium stock released at sea by reprocessing plant is returned to the atmosphere.